Nature for Sale Commons versus Commodities - Ricoveri, Giovanna (Pluto Press, 2013)
Uncovering the rich heritage of common ownership which existed before the dominance of capitalist property relations, Giovanna Ricoveri argues that the subsistence commons of the past can be reinvented today to provide an alternative to the current destructive economic order. Ricoveri outlines the distinct features of common ownership as it has existed in history through cooperatives, sustainable use of natural resources and direct democracy. In doing so, she shows how it is possible to provide goods and services which are not commodities exchanged on the capitalistic market, something still demonstrated today in village communities across the global South.Tracing the erosion of the commons from the European enclosures at the dawn of the Industrial Revolution to the new enclosures of modern capitalism, the book concludes by arguing that a new commons is needed today. It will be essential reading for activists as well as students and academics in history, politics, economics and development studies.